The Plight of Athletic Training Graduates in a Third World Country: An Obscure and Unregulated Profession in Jamaica - Van Der Rowe (Lithuanian Sports University, 2023)
Background: Sports treatment and rehabilitation in Jamaica appears to be a costly struggle for athletes of all ages, with very few facilities and specialists on the island. However, the introduction of the athletic training (AT) profession can bridge the gap in sports treatment and rehabilitation by creating a solid foundation for athletes, especially at the high school level. After 12 years of establishing the course of study in Jamaica, athletic trainers (ATs) are still not recognized and are unable to practice. Purpose: The purpose of this study was to highlight the aspirations of the athletic training profession in Jamaica. Methods: The study was conducted using an explanatory case study design that used an open-ended survey to collect data from AT graduates. A total of 20 participants were selected using a combined sampling method that utilized purposive and snowball sampling techniques. Google forms were used to create the open-ended questions and a content analysis method that utilized multi-analyst coding was used to establish relevant themes and categories from the responses. Results: The results of the study indicated that graduates are fnding it extremely difcult to get jobs as athletic trainers, due to the lack of awareness, promotion, and ambiguity of AT in Jamaica. Despite the challenges, graduates believed that a national AT association is crucial for seeking licensure and promoting awareness of the profession in Jamaica. Conclusion: If recognized, ATs can signifcantly help to boost sports treatment in Jamaica and contribute to greater sporting performances. Keywords: allied health professionals, athletic trainers, developing profession.